A rapid and simple clonality assay for bovine leukemia virus-infected cells by amplified fragment length polymorphism (AFLP) analysis - Kobayashi, Tomoko; Makimoto, Sakurako; Ohnuki, Nagaki; Hossain, Md Belal; Jahan, M. Ishrat; Matsuo, Misaki; Imakawa, Kazuhiko; Satou, Yorifumi (Microbiology spectrum, 2025)
Enzootic bovine leukosis (EBL) is routinely diagnosed based on external manifestations at the farm, such as the presence of tumors and/or general lymph node enlargement. However, due to the nonspecific clinical manifestations of EBL, over half of EBL cases are unrecognized at the farm, with most cases being diagnosed during postmortem inspection at the slaughterhouse. Early detection and monitoring of clonal expansion are necessary for managing EBL and reducing economic losses. In this study, we developed BLV-AFLP that represents a significant advancement in the diagnosis of EBL in cattle. This method can rapidly assess the clonal proliferation of BLV-infected cells, crucial for distinguishing between asymptomatic and EBL cattle. Additionally, tracking clonal dynamics offers insights into the disease’s progression, potentially providing strategies for avoiding economic losses. Overall, as BLV-AFLP is a simple and rapid test for detecting EBL, it is feasible and efficient for routine veterinary practice.